Simulação e controle do processo de produção de levedura - Reis, Giann Braune (2009)
The yeast Saccharomyces cerevisiae can be useful in several ways in bioprocesses. It is widely used in anaerobic processes for production of bioethanol at Brazilians plants. It is also of great importance as baker s yeast, where the product is the biomass. Moved by the industrial interest this work will aggregate knowledge in the improvement of techniques of control applied to bioprocesses, taking as a case study of aerobic yeast growth (process of obtaining biomass). This study developed a supervisory platform to perform the data acquisition and process control of a laboratory scale bioreactor. As case study experiments with Saccharomyces Cerevisiae were performed under aerobic conditions (looking for biomass obtainment). A fuzzy controller was developed and evaluated to control the input flow of supplemental medium (glucose) in bioreactor. The control variable was respiratory quotient (RQ). A sensor for the estimation of cell concentration in real time was evaluated and it shown to be effective for the application. It could provide information to the control algorithm. The experimental data obtained were used in the validation of a literature model. The result of simulation showed that the model satisfactorily described the studied process.